2018
DOI: 10.1001/jamaophthalmol.2018.0846
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Unverifiable Publications Among Ophthalmology Residency Applicants Invited to Interview

Abstract: IMPORTANCE Unverifiable publications in applications for ophthalmology residencies could be a serious concern if they represent publication dishonesty. OBJECTIVE To determine the rate of unverifiable publications among applicants offered an interview. DESIGN Retrospective review of 322 ophthalmology residency applications for entering classes 2012 to 2017 at Vanderbilt University School of Medicine, Nashville, Tennessee.INTERVENTIONS Full-length publications reported in the applications were searched in PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The authors checked the published journal articles and abstracts stated on candidate's urology, ophthalmology and neurosurgery training programme applications. The results were startling, revealing misrepresentation and sometimes complete fabrication of articles, with rates ranging from 5 to 45% [41][42][43]. It is of no surprise that commentary on these findings mentioned the competitiveness of these specialties as partial explanations for the transgressions, with similar findings from a Canadian study published in 2015 [44].…”
Section: The Relationship Between Research Misconduct and Medical Spementioning
confidence: 65%
“…The authors checked the published journal articles and abstracts stated on candidate's urology, ophthalmology and neurosurgery training programme applications. The results were startling, revealing misrepresentation and sometimes complete fabrication of articles, with rates ranging from 5 to 45% [41][42][43]. It is of no surprise that commentary on these findings mentioned the competitiveness of these specialties as partial explanations for the transgressions, with similar findings from a Canadian study published in 2015 [44].…”
Section: The Relationship Between Research Misconduct and Medical Spementioning
confidence: 65%
“…The need to reevaluate the merits of pre-residency publications is bolstered further by a study among ophthalmology applicants that revealed that up to 9.2% of applicants had at least one unverifiable publication on their application. 14 Furthermore, a study among Canadians applying for residency in a single surgical subspecialty found that 23% of applicants claiming publications had at least one misrepresented publication. 15 Another important finding of this study is the demonstration of a relationship between research productivity and career pursuits.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, do not encourage your advisees to embellish an experience or add something to their CV that they did not do. There is a growing body of literature speaking to "phantom publications," with an observation that 6-9% of applicants had unverifiable publications listed on their CV [18,19].…”
Section: Ethical Issues For Faculty Advisorsmentioning
confidence: 99%